SCHEDULING ON M PARALLEL MACHINES SUBJECT TO RANDOM BREAKDOWNS TO MINIMIZE EXPECTED MEAN FLOW TIME - (:unkn) unknown (JOHN WILEY & SONS INC, 1994)
The problem of scheduling n jobs on m parallel machines is considered when the machines are subject to random breakdowns and job processing times are random variables. An objective function of mean flow time is developed for a general parallel machine system, and an expression of its expected value is derived. The problem is transformed into a deterministic unrelated parallel machine scheduling model with modified processing times when the number of breakdowns is modeled as a generalized Poisson process. (C) 1994 John Wiley & Sons, Inc.
Keywords: EXPONENTIAL SERVICE TIMES; PROCESSORS; TASKS; JOBS